The analytics of the New Keynesian 3-equation Model - Poutineau, Jean-Christophe; Sobczak, Karolina; Vermandel, Gauthier (Economics and Business Review, 2015)
This paper aims at providing a self contained presentation of the ideas andsolution procedure of New Keynesian Macroeconomics models. Using the benchmark“3 equation model”, we introduce the reader to an intuitive, static version of the modelbefore incorporating more technical aspects associated with the dynamic nature of themodel. We then discuss the relative contribution of supply, demand and policy shocksto the fluctuations of activity, inflation and interest rate, depending on the key underlyingparameters of the economy.